Comparison of intrasession reliability and sensitivity across different deceleration-test results in male and female soccer players - Wei, X.; Zheng, X.; Zhu, H.; Vigh-Larsen, J. F.; Mohr, M.; Krustrup, P.; Chen, X. (International Journal of Sports Physiology and Performance, 2025)
Purpose: The aims of this study were to determine the deceleration abilities of male and female college soccer players and to examine the intrasession reliability and sensitivity and correlation between relevant deceleration-ability tests.